Using a multi-omic approach to investigate the mechanism of 12-bis-THA activity against Burkholderia thailandensis - Pattinson, Adam; Bahia, Sandeep; Le Gall, Gwénaëlle; Morris, Christopher J.; Harding, Sarah V.; McArthur, Michael (Frontiers in Microbiology, 2023)
Burkholderia pseudomallei is the causative agent of the tropical disease, melioidosis. It is intrinsically resistant to many antimicrobials and treatment requires an onerous regimen of intravenous and orally administered drugs. Relapse of disease and high rates of mortality following treatment are common, demonstrating the need for new anti-Burkholderia agents. The cationic bola-amphiphile, 12,12′-(dodecane-1,12-diyl) bis (9-amino-1,2,3,4-tetrahydroacridinium), referred to as 12-bis-THA, is a molecule with the potential to treat Burkholderia infections. 12-bis-THA spontaneously forms cationic nanoparticles that bind anionic phospholipids in the prokaryotic membrane and are readily internalised. In this study, we examine the antimicrobial activity of 12-bis-THA against strains of Burkholderia thailandensis. As B. pseudomallei produces a polysaccharide capsule we first examined if this extra barrier influenced the activity of 12-bis-THA which is known to act on the bacterial envelope. Therefore two strains of B. thailandensis were selected for further testing, strain E264 which does not produce a capsule and strain E555 which does produce a capsule that is chemically similar to that found in B. pseudomallei. In this study no difference in the minimum inhibitory concentration (MIC) was observed when capsulated (E555) and unencapsulated (E264) strains of B. thailandensis were compared, however time-kill analysis showed that the unencapsulated strain was more susceptible to 12-bis-THA. The presence of the capsule did not affect the membrane permeation of 12-bis-THA at MIC concentrations. Proteomic and metabolomic analyses showed that 12-bis-THA causes a shift in central metabolism away from glycolysis and glyoxylate cycle, and suppressed the production of the F1 domain of ATP synthase. In summary, we provide insight into the molecular mechanisms underpinning the activity of 12-bis-THA against B. thailandensis and discuss its potential for further development.